Design of Multidrug-Resistant Tuberculosis Treatment Regimens Based on DNA Sequencing. (26th April 2021) - Grobbel, Hans-Peter; Merker, Matthias; Köhler, Niklas; Andres, Sönke; Hoffmann, Harald; Heyckendorf, Jan; Reimann, Maja; Barilar, Ivan; Dreyer, Viola; Hillemann, Doris; Kalsdorf, Barbara; Kohl, Thomas A; et al.
Abstract: Background: Comprehensive and reliable drug susceptibility testing (DST) is urgently needed to provide adequate treatment regimens for patients with multidrug-resistant/rifampicin-resistant tuberculosis (MDR/RR-TB). We determined whether next-generation sequencing (NGS) analysis of Mycobacterium tuberculosis complex isolates and genes implicated in drug resistance can guide the design of effective MDR/RR-TB treatment regimens. Methods: NGS-based genomic DST predictions of M. tuberculosis complex isolates from MDR/RR-TB patients admitted to a TB reference center in Germany between 1 January 2015 and 30 April 2019 were compared with phenotypic DST results of mycobacteria growth indicator tubes (MGIT). Standardized treatment algorithms were applied to design individualized therapies based on either genomic or phenotypic DST results, and discrepancies were further evaluated by determination of minimal inhibitory drug concentrations (MICs) using Sensititre MYCOTBI and UKMYC microtiter plates. Results: In 70 patients with MDR/RR-TB, agreement among 1048 pairwise comparisons of genomic and phenotypic DST was 86.3%; 76 (7.2%) results were discordant, and 68 (6.5%) could not be evaluated due to the presence of polymorphisms with yet unknown implications for drug resistance. Importantly, 549 of 561 (97.9%) predictions of drug susceptibility were phenotypically confirmed in MGIT, and 27 of 64 (42.2%) false-positive results were linked to previously described mutations mediating a low or moderate MIC increase. Virtually all drugs (99.0%) used in combination therapies that were inferred from genomic DST were confirmed to be susceptible by phenotypic DST. Conclusions: NGS-based genomic DST can reliably guide the design of effective MDR/RR-TB treatment regimens. Abstract : Multidrug-resistant/rifampicin-resistant tuberculosis (MDR/RR-TB) treatment regimens selected on information of bacillary drug susceptibility predicted by pathogenomic next-generation sequencing showed high concordance to treatment regimens selected by phenotypic drug susceptibility testing and ensures timely initiation of rational, individualized MDR/RR-TB therapy.